Pengembangan Media Video Pembelajaran Biologi Sebagai Alternatif Peningkatan Kompetensi Dasar Siswa Saat Pandemi Covid-19 - Syarif Rizalia; Susilawati Susilawati; Widi Cahya Adi; Parlin Parlin (Institut Agama Islam Negeri Kendari, 2022)
The objectives of this development research are to produce video media for learning biology material for Covid-19 and synthesize the results of the validation of the Covid-19 biology learning video media as an alternative to increase students' basic competencies. The subject of this research is the biology teachers of class X at Kota Kendari. The results of the research shows that learning video media production went through seven stages, i.e., 1) analysis of potential and problems related to infrastructure at the research location; 2) data collection of scientific articles and modules; 3) product design; 4) validation of material designs by experts; 5) design improvements with consideration of advice from experts; 6) media product trial by teachers; and, 7) revision of media products with consideration from the teachers. The results of the validation of the learning video media are categorized as feasible. Therefore, the learning video media was potential to be developed as alternative media to foster the students’ basic competence of viral material.Keywords: Alternative media; basic competence; biology; Covid-19; learning video media.